Wellington : The Path to Victory 1769-1814 - Muir, Rory (New Haven Yale University Press, 2013)
The Duke of Wellington was Britain's greatest soldier, whose victories turned the tide of Napoleon's conquests and played a crucial role in his downfall. Wellington went on to be a major figure in British politics, twice serving as Prime Minister. Often the centre of controversy, he was at times feted and celebrated as a national hero, at others reviled in the press and abused in the streets. He was a far more complicated man than the paragon of virtue celebrated by Victorian biographers. Rory Muir's masterly new biography, the first of a two volume set, is the result of thirty years research into the Duke of Wellington and his times. The author brings Wellington into much sharper focus than ever before, critically examining every aspect of his life from his unhappy childhood, his baptism into British and Irish politics and his remarkable successes in India, to the setbacks and triumphs of the Peninsular War.
Include Maps, Illustrations, Chronology, Endnotes, Bibliography and Index.
The Path to Victory 1769-1814.
Keywords: Prime ministers -- Great Britain -- Politics and government